The Effect of Earnings Smoothing and Earnings Informativeness on Firm Value with Managerial Ability as a Moderating Variable - Sinuraya, Candra; Mayangsari, Sekar (International Journal of Economics and Financial Issues, 2024)
This study’s goal is to find out how earnings informability and income smoothing affect firm value, with managerial ability as a moderating variable. A quantitative method was used, and financial statements that were listed on the Indonesia Stock Exchange served as the source of the data. The sample population comprised 255 companies within the Consumer Non-Cyclicals and Consumer Cyclicals sectors, with a 4-year study period from 2017 to 2020. In addition, a total of 154 companies were selected based on the inclusion criteria, and 616 observations were carried out. This study used data from an emerging market country, namely Indonesia, which was known as the most promising investment destination. The results showed that earnings smoothing did not affect firm value, while earnings informativeness had a significant effect. The relationship between income smoothing and firm value was unaffected by managerial skill, even though it increased the correlation between earning informativeness and firm value. In line with these findings, company leaders must choose managers with high skills in financial management. These skills can greatly influence the impact of earnings informativeness on firm value.